A novel framework for quantifying the subject-specific three-dimensional residual stress field in the aortic wall. (January 2022) - Zhang, Ming; Liu, Haofei; Cai, Zongxi; Sun, Cuiru; Sun, Wei
Abstract: Background: Quantification of subject-specific residual stress field remains a challenge that prohibits accurate stress analysis and refined understanding of the biomechanical behavior of the aortic wall. Method: This study presents a framework combining experiments, constitutive modeling, and computer simulation to quantify the subject-specific three-dimensional residual stress field of the aortic wall. The material properties and residual deformations were acquired from the same porcine aortic sample, so that the subject-specific residual stress field was quantified analytically. Consequently, a novel stress-driven tissue growth model was developed and incorporated in a finite element aortic model to recover the subject-specific residual stress with the help of analytical solution. We then evaluated the framework's efficacy by simulating the residual stress distribution in the aortic dissection (AD). Result: Subject-specific residual stress field of the aortic sample was quantified analytically. No appreciable discrepancy was observed between the numerically simulated and analytically derived residual stress distributions, indicating the effectiveness of the tissue growth model. Errors arising from the numerically simulated circumferential opening angle and axial bending angle were within 5% relative to experimental results, highlighting that the framework was accurate in terms of subject-specific residual stress estimation. Finally, numerical simulations recovered the buckling behavior of the intimal flap of the dissected aorta and revealed the expansion of the false lumen and compression of the true lumen as the tear propagates circumferentially. Conclusion: The proposed framework is effective in quantifying the three-dimensional subject-specific residual stress field and it is potentially applicable in more sophisticated scenarios involving residual stress. Highlights: Residual deformations and material parameters acquired from the same aortic sample to ensure subject-specific residual stress. Propose a framework combining experiment, analytics and numerical simulation to evaluate the subject-specific residual stress. Experimentally-derived layer-specific residual deformations accurately replicated numerically with the proposed method. Residual stress in aortic dissection numerically simulated and buckling behavior of intimal flap validated against experiment.